S51 Heterogeneity of sputum and systemic inflammatory mediator profiles in bronchiectasis. (11th November 2022) - De Soyza, A; Smith, G; Killick, H; Guscott, M; Afzahl, Z; Bradley, J; Elborn, S; Cohen, S; Gavala, M; McCrae, C; Scott, IC; Kell, C
Abstract : Bronchiectasis is a complex and heterogenous disease. Recent findings have suggested in addition to a neutrophil predominant patient population there may be an eosinophil high bronchiectasis subpopulation. We hypothesised that more severe bronchiectasis is associated with inflammatory mediator dysregulation with either high levels of TH1 related cytokines and/or allergy/Th2 mediators. We also hypothesised that longitudinal analysis comparing stable state to exacerbation may identify exacerbation related signals. Methods: We analysed serum and PBS-sputum fraction from the BronchUK project (all Newcastle centre samples n = 165) and the Clinimetrics study (baseline samples only from a longitudinal study, and compared to clinical metadata such as age, hospitalisations, lung function, body mass index (BMI), exacerbations, Pseudomonas infection status and disease severity; Bronchiectasis severity index (BSI). Data such as FEV1% predicted was analysed as both a continuous variable and a categorical variable (FEV1 <30% predicted or >30% predicted as per BSI scoring). Adjustments were made for multiple comparisons using the Benjamini-Hochberg method and a threshold set at a False Discovery Rate of 0.05. Results: Considering serum and sputum inflammatory mediator levels, no sputum mediator showed statistically significant correlation with its corresponding serum levels. Correlation between different mediators sometimes reached statistical significance however, e.g. Serum IL-6, sputum TNF-Alpha, p adj = 0.001, r = 0.5. Overall, there were markedly more cytokines detected in sputum compared to serum. There were significant correlations between serum IL-6 and FEV1 (negative correlation, p adj =0.017, r = -0.3 and a positive correlation with breathlessness/MRCD (p adj =0.039, r = 0.26) No mediator either in sputum or serum correlated with BSI. Anti-inflammatory mediators such as VEGF and IL-10 were not significantly different in those with milder disease BSI scales. Conclusions: Bronchiectasis is heterogenous in inflammatory mediator profiles. Defining subpopulations and severity index requires further work – sputum sampling is likely required to identify therapeutics for specific subpopulations. Please refer to page A210 for declarations of interest related to this abstract.